HJP 272, an endothelin receptor antagonist, and its role in cancer cell migration and invasion - Nabeela Baig; Rameswari Chilamakuri; Saurabh Agarwal; Aaron Muth; Sandra E. Reznik (Translational Oncology)
Introduction: Endothelins (ETs) are a family of versatile peptides composed of 21 amino acids with three isoforms: ET-1, ET-2, and ET-3. As the most abundant of the three isoforms, ET-1 is involved in various biological processes, such as regulation of vascular tone, humoral homeostasis, and neural crest development. However, focus is now being directed towards investigating the functions of the ET axis in the progression of different tumor types including ovarian, prostate, breast, lungs etc. HJP 272 is a novel ETAR antagonist and while our group has previously researched its effects on lung inflammation and preterm birth, this study marks the first time its role in cancer has been explored. Methods: We evaluated the in vitro activities of HJP 272 in the ET-1 and ETAR overexpressing cell lines MDA-MB-231 (TNBC), and A549 (NSCLC). While HJP 272 had no effect on the viability of cancer cells, we observed a significant inhibition in the migration, invasion, and clonogenic capacities of both cell lines. RNA-seq and western blot data demonstrate the potential underlying molecular mechanisms of this compound in vitro. Furthermore, HJP 272 was evaluated in a 3D spheroid assay for its ability to inhibit tumor formation in both cell lines, revealing a significant change in MDA-MB-231 cells while no significant changes were observed in A549 cells. Conclusions: Our work indicates a therapeutic potential for HJP 272 in cancer metastasis. The distinct outcomes between the two cell lines shed light on the potential differences of HJP 272′s effects across multiple cancer types.